The Impact of Global Warming on U.S. Agriculture: An Econometric Analysis of Optimal Growing Conditions - Schlenker, Wolfram; Hanemann, W. Michael; Fisher, Anthony C. (The Review of Economics and Statistics, 2006)
We link farmland values to climatic, soil, and socioeconomic variables for counties east of the 100th meridian, the historic boundary of agriculture not primarily dependent on irrigation. Degree days, a non-linear transformation of the climatic variables suggested by agronomic experiments as more relevant to crop yield gives an improved fit and increased robustness. Estimated coefficients are consistent with the experimental results. The model is employed to estimate the potential impacts on farmland values for a range of recent warming scenarios. The predictions are very robust and more than 75% of the counties in our sample show a statistically significant effect, ranging from moderate gains to large losses, with losses in the aggregate that can become quite large under scenarios involving sustained heavy use of fossil fuels.